2010
DOI: 10.1038/ismej.2010.155
|View full text |Cite
|
Sign up to set email alerts
|

Capturing diversity of marine heterotrophic protists: one cell at a time

Abstract: Recent applications of culture-independent, molecular methods have revealed unexpectedly high diversity in a variety of functional and phylogenetic groups of microorganisms in the ocean. However, none of the existing research tools are free from significant limitations, such as PCR and cloning biases, low phylogenetic resolution and others. Here, we employed novel, single-cell sequencing techniques to assess the composition of small (o10 lm diameter), heterotrophic protists from the Gulf of Maine. Single cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 60 publications
4
76
0
Order By: Relevance
“…Arrows indicate taxa with contribution â©Ÿ 3% in both approaches (black), only by microscopy (white), or only by HTS (gray). Microscopy results are shown for dimensions compared with the pore size used for sample filtering or primer mismatches is not evident, but there could be other PCR bias (for example, selective amplification of closely-related species), taxon-specific susceptibility to DNA extraction or variability in the copy number of the rDNA operon (Medinger et al, 2010;Heywood et al, 2011). This supports known inconsistencies in relative abundances estimated by HTS and microscopy for ciliates and other protists (Bachy et al, 2013;Egge et al, 2013;Santoferrara et al, 2014;Stoeck et al, 2014).…”
Section: Comparison Of Tintinnid Morphospecies and Otussupporting
confidence: 62%
“…Arrows indicate taxa with contribution â©Ÿ 3% in both approaches (black), only by microscopy (white), or only by HTS (gray). Microscopy results are shown for dimensions compared with the pore size used for sample filtering or primer mismatches is not evident, but there could be other PCR bias (for example, selective amplification of closely-related species), taxon-specific susceptibility to DNA extraction or variability in the copy number of the rDNA operon (Medinger et al, 2010;Heywood et al, 2011). This supports known inconsistencies in relative abundances estimated by HTS and microscopy for ciliates and other protists (Bachy et al, 2013;Egge et al, 2013;Santoferrara et al, 2014;Stoeck et al, 2014).…”
Section: Comparison Of Tintinnid Morphospecies and Otussupporting
confidence: 62%
“…The picobiliphytes are a recently discovered group of pigmented protists that are related to telonemids, cryptophytes, and katablepharids (11, 34,45). A previous study found that the picobiliphytes may be underrepresented using conventional PCR-based clone libraries (26). Again, a lower gene copy number may have allowed their presence to be masked by the presence of eukaryotes with higher gene copy numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, heterotrophic protists were identified via culture-dependent and microscopic methods (62)(63)(64)(65). Recent studies have shown that a single-cell genomic approach can provide direct evidence of specific predator-prey interactions (66,67). We recovered 22 samples that had high levels of LysoTracker probe-associated fluorescence and were closely related to the stramenopile Pteridomonas danica ( Fig.…”
Section: Isolation and Description Of Two Key Photosynthetic Protistsmentioning
confidence: 99%